Effect of copper and magnesium on the microstructure of centrifugally cast al-19%si alloys - Contatori, Chester; Couto, Antonio Augusto; Vatavuk, Jan; Borges, Arnaldo A. Ciquielo; de Lima, Nelson Batista; Baldan, Renato [UNESP] (Trans Tech Publications, 2018)
Hypereutectic Al-Si alloys can be used in applications that require high wear resistance. Such wear resistance is achieved by the presence of hard primary silicon particles, allied to the formation of Mg2 Si intermetallic phase when magnesium is added in this alloy. Centrifugal casting generates a gradient in the microstructure of hypereutectic Al-Si alloys that can favor such applications. Cylindrical components of Al-19%Si alloy containing added copper and magnesium contents were processed by centrifugal casting. The purpose of this study is to investigate the formation and segregation of particles of primary silicon (β) and Mg2 Si in Al-19%Si alloy containing additions of copper and magnesium. Because the density of silicon (2.33 g/cm3 ) and Mg2 Si (1.88 g/cm3 ) is lower than that of aluminum (2.67 g/cm3 ), centrifugal casting causes primary silicon (β) and Mg2 Si particles to concentrate more at the outer wall of the centrifuged pipe. In this study, primary silicon (β) and Mg2Si particles were found to be retained at the outer wall of the pipe. It is believed that the rapid cooling of the molten metal in the region of contact with the mold, whose temperature is lower than that of the molten metal, allied to the centrifugal force, prevented the particles from migrating to the inner wall of the pipe. The microstructure shows a gradient in the distribution of these phases, enabling the production of a functionally graded material. The addition of copper and magnesium leads to the formation of Mg2 Si and Al5 Cu2 Mg8 Si6 phases, reducing the amount of primary β phase (Si) particles. In all the evaluated conditions, a tendency is also observed for a gradual increase in the segregation of silicon towards the inner wall along the entire length of the centrifuged pipe.
Keywords: Al-Si; Centrifugally cast; Functionally Graded Material